New putative animal reservoirs of SARS-CoV-2 in Italian fauna: A bioinformatic approach. Issue 11 (November 2020) - Buonocore, Michela; Marino, Carmen; Grimaldi, Manuela; Santoro, Angelo; Firoznezhad, Mohammad; Paciello, Orlando; Prisco, Francesco; D'Ursi, Anna Maria
Abstract: SARS-CoV-2 is a virus belonging to the betacoronavirus family, causing fatal respiratory disease in humans, which became pandemic in 2020. Italy is one of the most affected countries by COVID-19, particularly in the northern regions. Several studies consider COVID-19 a zoonotic disease and, since Italy is the repository of a high biodiversity, SARS-CoV-2 infection in animals can be considered as a reservoir of the virus or favor the spreading between animals and humans. In this work, we analyzed the amino acid sequences of ACE2 protein of the most common domestic and wild animals present in Italy. Among the latter, we focused on ACE2 of the Chiroptera species present in Italy to identify the primary reservoir in this region. First, we reproduced in silico the Chiroptera ACE2/viral spike (S) protein interactions on the human ACE2/SARS-CoV-2 S complex model and identified the critical residues for the binding. In silico molecular docking of ACE2 belonging to Chiroptera vs SARS-CoV-2 S protein pointed to Rhinolophus ferrumequinum as a bat living in Italy, that may be a potential primary reservoir of the virus. On the other hand, a sequence similarity search on ACE2 of domestic and wild animals living in Italy pointed to domestic (horses, cats, cattle and sheep) and wild (European rabbits and grizzly bears) animal species as potential SARS-CoV-2 secondary reservoirs. Molecular docking of ACE2 belonging to these species vs S protein of Bat coronavirus (Bt-CoV/Rp3/2004) suggests that the primary reservoir Rhinolophus ferrumequinum may infect the secondary reservoirs, domestic and worldwide animals living in Italy, determining a specific risk of SARS-CoV-2 infection. Abstract : Bioinformatics; Virology; SARS-CoV-2; COVID-19; Italian biodiversity; molecular docking and dynamics; sequence alignment; host range prediction.